A Method for Quantitative Evaluation of Seismic Stability of Loess Slope Based on the Shaking Table Model Test. (3rd December 2021) - Xiaowu, Pu; Lanmin, Wang; Ping, Wang; Shaofeng, Chai; Shiyang, Xu
Abstract : The large-scale shaking table model test, which can directly reproduce the process of slope instability and failure, is an important technical means for the prediction and evaluation of slope seismic stability. However, up to now, the systematic slope stability evaluation method based on the shaking table slope model test has not been established, which limits the application of the expensive shaking table model test in slope seismic design. Therefore, the slope stability evaluation method based on the model test needs to be developed and innovated. In this research, through three loess slope model tests with different rainfall, according to the change law of the peak value of transfer function spectrum, combined with the macrodestructive characteristics of the slope model, an accurate calculation method of the critical instability acceleration of the slope is proposed. Based on the behavior similarity theory, for the shaking table model test of slope whose soil cohesion cannot meet the similarity ratio, the reduction method of applying the critical instability acceleration obtained from the model test to prototype slope is proposed. Based on first-order natural frequency and damping ratio extracted from the TF spectrum curve, a calculation method for the stability factor F s of loess slope based on the shaking table model test is proposed, and the stability factors of loess slope under the action of different seismic ground motion would be quantitatively calculated. The above methods provide another effective way for qualitative prediction and evaluation of seismic stability of loess slope.